The Root of all Evil? Money and the Scottish Catholic Mission in the Eighteenth Century - McMillan, J. F. (Studies in church history, 1987)
We are all familiar with the idea that the Church is in the world but not of it, and that too great a preoccupation with earthly things may compromise the Church’s other-worldly objectives. One thinks of the extravagance of a Renaissance pope such as Leo X, reputed to have said, ‘Let us enjoy the papacy, since God has given it to us’: or of an ancien régime prelate like the Archbishop of Mainz, who arrived for the coronation of the Emperor Joseph II with a retinue of fourteen sumptuous carriages: or, in our own time, the Vatican’s reported links with some of the shadier elements in the world of international finance. Yet, it is equally obvious that lack of adequate material resources can act as a serious impediment to the Church’s mission to go forth and teach all nations. Excessive poverty, like excessive wealth, brings its own problems. As the adage has it, not money itself but the desire for money is the root of all evil. Excessive poverty and the desire for money are the themes which I wish to pursue in this paper, in the context of the Scottish Catholic Mission in the eighteenth century, and more specifically as they relate to the so-called Jansenist quarrels which divided the Mission in the 1730s and 1740s.